Ionic liquid mixtures with tunable physicochemical properties. (1st January 2015) - Moreno, J. Serra; Jeremias, S.; Moretti, A.; Panero, S.; Passerini, S.; Scrosati, B.; Appetecchi, G.B.
Graphical abstract: The possibility to prepare ionic liquids with improved or particular characteristics by properly combining/tuning pure materials was investigated. These ionic liquid mixtures might be appealing as electrolyte components for electrochemical devices operating under hard conditions, not always achievable by single materials. ABSTRACT: Innovative ionic liquids (ILs) can be prepared by properly combining pure ILs, thus obtaining materials with improved characteristics. For instance, three different mixture families, namely PYR11 TFSI-PYR14 TFSI, PYR11 TFSI-PYR18 TFSI and PYR14 TFSI-PYR18 TFSI, were prepared and investigated in terms of thermal behavior, ionic conductivity and ion self-diffusion coefficient as a function of the mole composition. The physicochemical properties, including mechanical consistency, of these mixed ionic liquids were found to be enhanced and/or finely tuned by properly varying the aliphatic chain length and/or the mole ratio of the pyrrolidinium cations. This issue might be profitably exploited to match the electrolyte requirements of electrochemical devices operating under particular or hard conditions, not always achievable by single materials.